Indonesian–English Code Mixing in Scarlett Ads: A Study of Creative Language Strategy in Digital Marketing - Septi Sabilla Rahmawati; Otong Setiawan Djuharie (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study examines the use of Indonesian–English code-mixing in digital advertisements for Scarlett Whitening on Instagram, with the aim of identifying the structural types of code-mixing employed and analyzing its function as a creative language strategy in digital marketing. A descriptive qualitative approach was adopted, drawing on eight poster headlines published on the official @scarlettofficial Instagram account between June 2024 and February 2025. The data were analyzed using Muysken’s (2000) typology of code-mixing—which comprises insertion, alternation, and congruent lexicalization—and interpreted through Hoffman’s (1991) functional framework, which distinguishes topical, interjectional, and emphatic motivations. The findings reveal that insertion is the most dominant structural type, occurring in the majority of advertisements through the embedding of English nouns and adjectives into Indonesian syntactic frames. Alternation appears in two advertisements featuring structurally complete English clauses, while congruent lexicalization is identified in a single instance involving the morphological blending of an English compound noun with an Indonesian suffix. Functionally, English insertions serve three primary purposes: they address topical domains where English terminology is more widely recognized, establish interjectional intimacy through informal address terms, and function emphatically to create exclusivity and rhetorical impact. The study concludes that code-mixing in Scarlett’s advertisements is not an incidental linguistic occurrence but a deliberate strategic instrument for projecting modernity, technical credibility, and social relatability, thereby effectively balancing global appeal with local accessibility in the competitive digital beauty market.